MASALAH YANG DIHADAPI SISWA SEKOLAH DASAR NEGERI 005 DESA BARU KECAMATAN SIAK HULU KABUPATENKAMPAR - Zali, Abdul; ', Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study is aimed at 1) finding out the description of students' personal problems including both male and female. 2) finding out the description of students' emotional problems including both male and female 3) finding out the description of students’ learning problems including both male and female. 4) finding out the description of students' familial problems including both male and female. 5) finding out the description of students' social problems including both male and female. 6) finding out the description of overall students' problems. 7) finding out the category of students' problems in general. The data dealing with student problem preferences based on personal, emotional, learning, familial, and social aspects were collected by using questionnaire. The subjects of the research are 200 students of State Elementary School 005 Baru Village, Siak Hulu Sub district whose choise were based on sex. The sampling technique is the total one. The research results showed that: 1) 60 moderate category male students (59%) and 55 moderate category female students (56%) experienced personal problems. 2) 97 moderate category male students (96%) and 91 moderate category female students (92%) experienced emotional problems. 3) 69 moderate category male students (68%) and 71 moderate category female students (72%) experienced learning problems. 4) 70 moderate category male students (69%) and 69 moderate category female students (70%) experienced familial problems. 5) 53 moderate category male students (52%) and 50 moderate category female students (51%) experienced social problems. 6) 97% male students and 91% female students experienced emotional problems, 70% male and 69% female students experienced familial problems, and 69% and 71% male and female students experienced learning problems. 7) In general, the problems experienced by male students and female students are emotional, familial and social in moderate category.Keywords: Problems of Students